Variation in chemical components of aquacultured Ulva (Chlorophyta) in response to environmental variables - Etwarysing, Lekraj (Marine Research (MA-RE) Institute, 2016)
A detailed literature review of relevant Ulva biology and chemical composition is included. Marine algae are known to produce a wide range of volatile organic compounds that are primarily used in chemical communications. These compounds are released in seawater and act as either pheromones or allelochemicals. Aldehydes have been reported to be the main group of volatile compounds in green algae Ulva. Cultivation of Ulva as feed on abalone farms in South Africa has been a success but there has been little research on the chemistry of South African Ulva. This study aims to investigate the potential effects of environmental variables and grazing on the chemical profile, and specifically on the aldehyde-type natural products produced (δH 9.00 - 10.50) by laboratory cultured Ulva using ¹H NMR spectroscopy and multivariate statistical analysis. Ulva armoricana was cultured at different salinities: 5, 10, 20, 25 and 35 ‰ (all ± 0.1 ‰) and nutrient treatments: 100 % Provasoli ES medium (high nutrient supply) and 0 % Provasoli ES medium (low nutrient supply) at 10 °C and 15 °C for 6 days under constant light (39.2 ± 0.43 μmol photons m⁻² s⁻¹) on a 16:8 hours light:dark photoperiod. Natural grazing (using Tricolia capensis Dunker) and artificial grazing (stimulated by scissors) was performed to determine their effects on the chemical composition of Ulva armoricana. Results obtained show that grazing and nutrient experiments mostly affected the aromatic, hydroxylic and carbonyl compounds regions, while salinity change mostly affected the alcohol, ester and phenolic regions. The aldehyde profiles included a prominent peak at δH 9.76 in almost all treatments that was provisionally identified as hexanal. Ulva armoricana grown at 10 °C under low nutrient condition and in a medium with salinity at 25 ‰ was found to be the ideal condition to produce a higher intensity of the main aldehyde.